Emergency Contraceptives: Knowledge and Practice towards Its Use among Ethiopian Female College Graduating Students - Mishore, Kirubel Minsamo; Woldemariam, Abebaw Demissie; Huluka, Solomon Assefa (International Journal of Reproductive Medicine, 2019)
Introduction. Ethiopia has a high incidence of unwanted pregnancies and incomplete and unsafe abortions, particularly among adolescents. This can be avoided by using different contraceptive methods including emergency contraceptives (EC). This study aimed to assess the knowledge and practice of EC among female college graduating students in Harar, Eastern Ethiopia. Methods. Institution based cross-sectional study was conducted on 214 female students selected from two randomly selected colleges. Data was collected using a self-administered questionnaire and analyzed using SPSS for Windows version 20.1. Level of significance was taken at P <0.05. Results. The mean (±SD) age of the participants was 21.06 (±2.14) years. Of the 200 (93.5%) study participants who had ever heard of ECs, 140 (70.0%) had good knowledge. Among the 214 graduating female students, 66 (33.0%) had ever used EC. Being above the age of 20 years old, father’s and mother’s literacy were found to be determinants of knowledge of EC. Moreover, knowledge was the only determinant factor of practice of EC. Conclusion. Most of the respondents had relatively good knowledge of EC. The study revealed that female students of older age and higher educational status of parents had higher knowledge and practice of EC.